Activation of MAP kinases by calcium-dependent and calcium-independent pathways. Stimulation by thapsigargin and epidermal growth factor. - Tan Chao; Kenneth L. Byron; Kyung‐Mi Lee; M L Villereal; Marsha Rich Rosner (1992)
In order to determine the effect of calcium mobilization on mitogen-activated protein (MAP) kinase activation, we have treated human foreskin fibroblasts (HSWP cells) and human epidermal carcinoma (A431) cells with thapsigargin. Intracellular free calcium was monitored by single cell image analysis using fura-2 and correlated with MAP kinase stimulation as assessed by immunoprecipitation, kinase renaturation assays and immunoblotting. Thapsigargin stimulated the 44- and 42-kDa MAP kinase isozymes in both cell types with kinetics that were slightly delayed relative to enzyme stimulated by epidermal growth factor. Removal of external calcium did not significantly affect the activation of the MAP kinases by thapsigargin, indicating that intracellular calcium mobilization is sufficient to stimulate the enzymes. However, treatment of cells with EGTA under conditions which deplete both intra- and extracellular calcium inhibited stimulation by thapsigargin but not epidermal growth factor. Stimulation of the MAP kinases by the calcium ionophore ionomycin paralleled the activation observed with thapsigargin in both calcium-containing and calcium-free conditions. These results indicate that there are at least two independent pathways for stimulation of MAP kinase: one that is dependent on intracellular calcium mobilization, and one that is mediated by the tyrosine kinase epidermal growth factor receptor and is calcium-independent.